Alda Merini: la scelta della follia, la salvezza della parola - Redaelli, Stefano (Romanica Silesiana)
Alda Merini: The Choice of Madness, the Rescue of the Word Alda Merini’s early vocation to poetry produced a twofold clash with society: as a woman and as a poet. Madness was for her both a choice of otherness (as the choice of living homeless) and diagnosis: a sentence by society to her disadvantage. Through and notwithstanding the experience of mental illness, of imprisonment in a psychiatric hospital, and of the consequent stigma, Alda Merini was able to build up her identity. Against the power mechanisms of psychiatry and against social exclusion, she grabbed the sword of writing. Thanks to writing (which is therapy and singing) Alda Merini did not let the hell experience of the psychiatric hospital and the stigma of illness overcome her. She was able, in this way, to realize her vocation as woman and poet. Key words: poetry, madness, woman, vocation, identity.